2007
DOI: 10.1007/s11192-008-0220-2
|View full text |Cite
|
Sign up to set email alerts
|

A new look at evidence of scholarly citation in citation indexes and from web sources

Abstract: A sample of 1,483 publications, representative of the scholarly production of LIS faculty, was searched in Web of Science (WoS), Google, and Google Scholar. The median number of citations found through WoS was zero for all types of publications except book chapters; the median for Google Scholar ranged from 1 for print/subscription journal articles to 3 for books and book chapters. For Google the median number of citations ranged from 9 for conference papers to 41 for books. A sample of the web citations was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 19 publications
1
37
0
1
Order By: Relevance
“…Noruzi (2005) studied the citation counts in Google Scholar and Web of Science of 36 webometrics papers; in most cases, he found that Google Scholar provided higher citation counts than Web of Science. These findings were corroborated by the results of Vaughan and Shaw (2008) for information science. Bakkalbasi, Bauer, Glover, and Wang (2006) compared citation counts for articles from 11 oncology journals and 11 condensed matter physics journals published in 1993 and 2003.…”
Section: Literature Reviewsupporting
confidence: 73%
“…Noruzi (2005) studied the citation counts in Google Scholar and Web of Science of 36 webometrics papers; in most cases, he found that Google Scholar provided higher citation counts than Web of Science. These findings were corroborated by the results of Vaughan and Shaw (2008) for information science. Bakkalbasi, Bauer, Glover, and Wang (2006) compared citation counts for articles from 11 oncology journals and 11 condensed matter physics journals published in 1993 and 2003.…”
Section: Literature Reviewsupporting
confidence: 73%
“…However, even four years after its introduction, Vaughan and Shaw (2008) found that 92% of Google Scholar citations in the field of library and information science represented what they called "intellectual impact", and that most citations came from journal articles. In the largest published verification project to date, the London School of Economics project on impact in the Social Sciences (2011), Google Scholar citations were collated for all traceable publications of a sample of 120 academics spread across five social science disciplines.…”
Section: Data Sources and Proceduresmentioning
confidence: 99%
“…Many researchers have employed an implicit type of web citation by using Google Scholar to calculate citation counts to articles (Jascó, 2005;Mayr & Walter, 2007;Meho & Yang, 2007;Vaughan & Shaw, 2008). The results correlate significantly with Web of Science citations (Kousha & Thelwall, 2007) and incorporate a range of source documents, including, but not limited to, publishers' digital libraries.…”
Section: Web Citationsmentioning
confidence: 99%